Risk Factors for Sexual Harassment in Public Places - Anwar, Farida; Österman, Karin; Björkqvist, Kaj (Technium Social Sciences Journal, 2020)
The aim of the study was to investigate risk factors for victimisation from sexual harassment in public places. A questionnaire was completed by 591 female university students in Finland. The mean age was 25.2 years (SD = 7.1). Nonverbal sexual harassment was found to be the most common type of sexual harassment, followed by physical. The most common place of victimisation was in a nightclub or bar, and the most common perpetrator was a stranger. The most common single acts of victimisation were to be stared at with filthy looks and talked to in an unpleasant sexual way. Victimisation from sexual harassment in public places was significantly predicted by physical punishment during childhood, victimisation from peer aggression at school, victimisation from verbal and physical intimate partner aggression, and low self-esteem. When frequency of sexual harassment was controlled for, emotional distress caused by sexual harassment correlated significantly with victimisation from verbal intimate partner aggression, victimisation from peer aggression at school, and a low self-esteem, suggesting sensitisation to aggression. In this sample of Finnish university students, the levels of victimisation from sexual harassment were low. Victimisation from other types of aggression and low self-esteem were identified as possible risk factors for victimisation from sexual harassment.